خواتین مصنفین اور حوا کی کہانی: تانیثی، نسائی یا پدر سری (Al-Qamar, 2024)
This research paper discusses the retelling of the Qur’anic story of Adam and Eve by women writers to understand the form of women consciousness involved in the retelling of the story. This paper tries to explore different aspects of the Qur’anic narrative that have been used as symbols and metaphors by women writers. The fiction written by Pakistani women writers is included in this study. The study refers to the theoretical position of feminist theologians to ascertain the feminist form of women consciousness. It is concluded that the purely patriarchal interpretations are accepted and used in the retelling and there is no feminist position, critique or deconstruction seen.
Keywords: Adam; Eve; Hawwa; feminine; feminist; female; patriarchal; theology; feminist theology; women writers